FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT DELAY PADA PERUSAHAAN PERBANKAN - Zebriyanti, Devi Eka; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to test the influence profitability, leverage, firm size, auditor opinion, and the size of Public Accountant Office to the audit delay. The population is all banking companies which are listed in Indonesia Stock Exchange (IDX) in 2010-2014 periods. The sample collection technique has been done by using purposive sampling which is done by selecting sample based on certain criteria which is desired by the researcher. The samples are 31 companies with five years observation period so 155 observation objects have been selected. The data is the secondary data in the form of annual financial statement of the company which has been obtained from Indonesia Stock Exchange (IDX). The data analysis technique has been done by using multiple linear regressions and its significance level is 5%. The result of the research shows that firm size and the size of public accountant has negative influence to the audit delay. Meanwhile, profitability, leverage and auditor opinion do not have any influence to the audit delay.Keywords : Profitability, Leverage, Firm Size, Auditor Opinion, Size of Public Accountant Office